The Effects of Three Learning Models of Hindu Religious Education on Students' Critical Thinking and Their Spiritual Attitudes - I Wayan Santyasa; Ida Ayu Gde Yadnyawati; I Ketut Suda (International Journal of Interreligious and Intercultural Studies, 2022)
This research reconstructed three learning models, i.e: social reconstruction model (SRM), open model (OM), and academic model (AM). The purpose of this research is to analyze the effect of the three learning models on critical thinking and spirituality attitude. This research was conducted with a non-equivalence post-test only control group design. The population was 638 students of Universitas Pendidikan Ganesha who studied Hinduism in odd semesters in the Academic Year 2021/2022. The sample was 174 students which were divided into three groups consisting of 58 students, each group studied with the SRM, OM, and AM models. The study groups is determined by a random technique. To measure of spirituality attitude, a questionnaire was used, while to measure students' critical thinking, a critical thinking test was used. To analyze the data, MANOVA was used. The results showed: 1) The effect of SRM is greater than the effect of OM on critical thinking; 2) the effect of SRM is greater than the effect of AM on critical thinking; 3) there is no difference in the effect of OM and AM on critical thinking; 4) SRM’s effect is equal to the OM’s effect on spirituality attitude; 5) the effect of SRM is greater than the effect of AM on spirituality attitude; 6) OM's effect is greater than AM's effect on spirituality attitude. The SRM is the best choice for Hindu Religious Education in order to achieve students’ critical thinking and their spirituality attitude optimally.